2019
DOI: 10.11124/jbisrir-2017-003879
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of triage quality in the emergency department: a scoping review protocol

Abstract: Review objective/questions: The objective of this scoping review is to explore the existing literature on the evaluation of the quality of triage for patients of all ages and medical conditions in emergency departments (EDs). The question for this review is: How is triage in the ED evaluated? More specifically, we are interested in answering the following sub-questions:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…30 Jeppesen et al 31 reported that while an under-triage rate of less than 5% in trauma cases is often considered acceptable, actual rates vary between 13% and 28%, 30,31 confirming the importance of accurate triage as a high priority. A scoping review suggests that triage is a critical indicator of quality care in EDs, 32 yet the nursing sensitivity of reported indicators is questionable, as many are subject to environmental factors. We suggest that both accuracy in triage overall and the identification of high-risk patients at triage are independent QIs and a reflection of the education and experience of individual nurses and the socioclinical culture of the ED.…”
Section: Discussionmentioning
confidence: 99%
“…30 Jeppesen et al 31 reported that while an under-triage rate of less than 5% in trauma cases is often considered acceptable, actual rates vary between 13% and 28%, 30,31 confirming the importance of accurate triage as a high priority. A scoping review suggests that triage is a critical indicator of quality care in EDs, 32 yet the nursing sensitivity of reported indicators is questionable, as many are subject to environmental factors. We suggest that both accuracy in triage overall and the identification of high-risk patients at triage are independent QIs and a reflection of the education and experience of individual nurses and the socioclinical culture of the ED.…”
Section: Discussionmentioning
confidence: 99%
“…A ccurate triage decision-making is a critical indicator of quality in the emergency department (ED). 1 While all ED patients benefit from timely access to necessary resources, geriatric patients (ie, those older than 65 years) have unique and complex care needs spanning medical, cognitive, emotional, social, and environmental domains. 2 Timely ED access is generally facilitated using a standardized triage process, an almost exclusively nursing function.…”
mentioning
confidence: 99%
“…Undertriage is associated with a significantly higher rate of hospital admission and critical outcomes, while overtriage is associated with a lower rate of both, 11 suggesting that effective triage, resulting in the rapid and accurate identification of critically ill patients, is a valid indicator of quality care in EDs. 1 Currently, triage accuracy is not designated as a quality indicator.…”
mentioning
confidence: 99%
See 1 more Smart Citation